Exploration of Tanimbar Local Wisdom in the Development of SMP Mathematics Books - Mesak Ratuanik; Samuel Urath; Pesparani Diana Jabar; Inda A Batbual; Thobias Melmambessy; Baceria Werluka; Vendalina Kdise (Bakti : Jurnal Pengabdian Kepada Masyarakat, 2024)
Local wisdom is seen as relevant to mathematics learning, because local wisdom is a cultural product which includes philosophy, values, norms, ethics, rituals, beliefs, habits, customs, and so on. Mathematical concepts introduce children to different ideas, beliefs, values, and cultures and even relate to teaching children values and attitudes. The local wisdom (culture) found in the Tanimbar Islands Regency is Tanimbar woven cloth, wickerwork, traditional houses, fine art statues and ancestral relics. The culture found in the Tanimbar Islands Regency contains aspects of mathematics that can be used as a learning resource by educators and students. This indicated local wisdom (culture) can be used as a source of material and values which can be used as a basis for direction of action and behavior in everyday life. Therefore, one of the appropriate strategies in dealing with problems that occur in learning is to explore the local wisdom of Tanimbar in developing mathematics textbooks. The learning book developed is deemed to be in accordance with the needs in the field based on local wisdom such as mathematical aspects found in Tanimbar woven cloth, wickerwork, Tanimbar traditional houses, fine art statues and preserved ancestral relics. Researchers believe that models developed based on local wisdom can improve the quality of mathematics learning in terms of students' knowledge and attitudes.